Integrating Game-based Interactive Media as Instructional Media: Students’ Response - Dwi Yuniasih Saputri; Rukayah Rukayah Rukayah; Mintasih Indriayu Indriayu (Intelektual Pustaka Media Utama, 2018)
Instructional media functioning to deliver the lesson has a very important role. There are a lot of instructional media used in learning process; one of those is interactive multimedia. This study aims to find out students response toward game based interactive media as instructional media in elementary school. The method used in this study was descriptive qualitative. The sample in this study was 10 students 5th grade elementary school. The data collecting methods were interview, observation and questionnaire. The collected data were analyzed by using interactive analysis consist of data collecting, data reduction, data presenting and conclusion. The result of this study shows that the student gave a good response toward game-based interactive multimedia. The students like and support the use of game based interactive multimedia as instructional media. Students felt that it was easier to understand lesson because the lesson was delivered not only through text, but also picture, audio, video and animation. The game in interactive media make the student be entertained and active in learning process. It is suggested that the teacher cooperate with the expert in education technology to improve interactive multimedia as interaction media.